Management Accounting Principles (Book). - Zeff, Stephen A.; Rappaport, Alfred; Moonitz, Maurice; S. A. Z.; Boutell, Wayne S.; Stimpson, W. Arthur; Hoffman, William H.; Shillinglaw, Gordon; Perry, Kenneth W.; Murphy, James T. (The Accounting Review, 1966)
The article focuses on several books related to accounting. Some of the books mentioned are, "Management Accounting Principles," by Robert N. Anthony, is identical in organization and presents several accounting problems and cases; "The Theory of Profit Determination on Long Term Contracts and an Appraisal of Australian Practice," by G.W. Beck, states that the percentage-of-completion method is the proper one for the determination of periodic profit on long-term contracts; "The Valuation of Property," by James C. Bonbright is a contribution in the field of applied and Institutional economics; "Management Information and Accounting," by R. Warwick focuses on cost accounting, which for a number of years has been a phenomena in transition; "SEC Accounting Practice and Procedure," second ed., by Louis H. Rappaport, presents information on current accounting practices and SEC policies in the U.S.; "Essentials of Financial Management," by Ernest W. Walker, covers the range of topics usually found in the popular finance texts, and at the same time presents a concise statement on managerial finance.